Performance Evaluation of Chili (Capsicum Annum L.) Genotypes Under Mid-Hill Agro-climatic Conditions of Kirtipur, Nepal - Adhikari, Spriya; Ghimire, Deepika (Nepalese Journal of Agricultural Sciences, 2026)
A study was conducted to evaluate ten chili pepper genotypes for yield performance under Preliminary trial in Kirtipur, Himalayan College of Agricultural Sciences and Technology, from March to July 2025. The genotypes, including Karma 747, Nepa Hot, Karma 777, Anna 3, Big Mama, Omega, Super Tara, Sudra, Premium, and the check variety ‘Pusa Jwala’, were evaluated in an open field using a Randomized Complete Block Design (RCBD) with three replications. The genotype Nepa Hot demonstrated the highest productivity (16.60 t/ha). It was an early-maturing variety, reaching 50% flowering in 47 days and 50% fruiting in 55 days. Despite having smaller fruits (length: 4.08 cm, width: 15.89 mm), its high fruit set resulted in superior yield. In contrast, Big Mama yielded the lowest (8.43 t/ha). Other promising genotypes included Super Tara, Omega, and Premium. The study identifies Nepa Hot as a prime candidate for farmer-led field trials and subsequent varietal release, promising to enhance chili productivity and sustainability in the mid-hills of Nepal, Kirtipur.